2012
DOI: 10.1021/cn200113z
|View full text |Cite
|
Sign up to set email alerts
|

Potential of a γ-Glutamyl-Transpeptidase-Stable Glutathione Analogue against Amyloid-β Toxicity

Abstract: The antioxidant properties of glutathione (GSH) and their relevance to oxidative stress induced pathological states such as Alzheimer's disease is well-established. The utility of GSH itself as a pharmacotherapeutic agent for such disorders is limited because of the former's lability to breakdown through amide cleavage by the ubiquitous enzyme γ-glutamyl transpeptidase (γ-GT). In the present study, a GSH analogue, Ψ-GSH, where the γ-glutamylcysteine amide linkage is replaced with a ureide linkage, was synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 31 publications
(63 reference statements)
1
36
0
Order By: Relevance
“…ψ-GSH ( Figure S1 ) was synthesized in our laboratory using a previously described synthetic method [ 16 ]. Authentication of the compound was through NMR analysis and purity (>97% pure) of ψ-GSH was confirmed by reverse phase HPLC analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ψ-GSH ( Figure S1 ) was synthesized in our laboratory using a previously described synthetic method [ 16 ]. Authentication of the compound was through NMR analysis and purity (>97% pure) of ψ-GSH was confirmed by reverse phase HPLC analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, attempts to promote GSH synthesis by providing precursors also failed due to inadequate biosynthetic machinery in the aging brain [ 15 ]. We formulated and successfully tested a solution to this problem through the design and synthesis of a metabolically stable GSH analog, ψ-GSH ( Figure S1 ), which is (a) resistant to cleavage by GGT, (b) able to utilize the GSH influx transporters at the Blood Brain Barrier (BBB), (c) substitute for GSH as a cofactor in Glo (and other GSH dependent) enzyme reactions, and (d) act as an antioxidant against H 2 O 2 insult [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progressive build-up of A β in and around vessels induces alteration in the BBB permeability, which chronically limits blood supply and results in deprivation of oxygen and nutrients 12 , 13 . Accordingly, these changes trigger a secondary cascade of metabolic events involving generation of free radicals, oxidative stress, and release of proteases, such as γ -glutamyl transpeptidase ( γ -GT) and alkaline phosphatase (ALP) 13 , 14 , 15 . Therefore, BMECs are considered as a potential target in AD.…”
Section: Introductionmentioning
confidence: 99%
“…-Glutathione (psi-GSH) is a stable glutathione analogue, in which the amide bond is replaced by a ureide linkage. It crossed the blood-brain barrier via the glutathione active uptake machinery, protected cells against chemical oxidative insult and lowered the cytotoxicity of A␤ [450]. Researchers of the University of Minnesota (Minneapolis, MN) showed that the restoration of glyoxalase enzyme activity precluded cognitive dysfunction in AD mice [451].…”
Section: Nootropics ("Drugs Without Mechanism")mentioning
confidence: 99%